Global higher education practices in times of crisis : questions for sustainability and digitalization - Hack-Polay, Dieu; Lock, Deborah; Caputo, Andrea; Lokhande, Madhavi; Salunkhe, Uday (Bingley, U.K. : Emerald Publishing Limited, 2024)
COVID-19 has challenged the international environ of higher education teaching, leading colleagues and institutions across the globe to think outside the box and develop innovative practices suited for turbulent times. But often, these are confined to the local or regional levels. Taking forward the notion of the scholar without borders, Global Higher Education Practices in Times of Crisis provides a critical review of the teaching practices in international higher education in the post-COVID era. Issues and debates about inclusivity, diversity, and cultural representation in the curriculum and classroom are explored through the eyes of the academics who negotiate complex teaching landscapes either on a temporary or permanent basis. The aspiration for universal nuanced teaching practices which reflect individual and national identities, along with newly emerging global ones that represent virtual academic citizenship that cross geographical and political borders, are presented as a foundation on which to instil borderless higher education.
Introduction / Dieu Hack-Polay, Deborah Lock, Andrea Caputo, and Mahdavi Lokhande -- Chapter 1. Next-generation innovative teaching ecosystems for futuristic management education / Ragini N Mohanty, Anu Thomas, and Abhishek Kori -- Chapter 2. Teaching in times of crisis or pandemic pedagogy snezhana chernova / J-F, Darren Pullen, Andy Bown, Zi Siang See , Naomi Nelson, Anita Heywood, Loan Dao, Yang Yang, Helena Winnberg, Stacie Reck -- Chapter 3. Using design thinking to redesign the student learning experience: The case of higher education / Farah Arkadan and Niloofar Kazemargi -- Chapter 4. Educational innovation and digitalisation during crises / Jai Raj Nair -- Chapter 5. Resilience and the entrepreneurial university during turbulent times: A model for the higher education sector / Kiran Vazirani, Rameesha Kalra, and Gnanendra M -- Chapter 6. Higher education in times of crisis: Shifting towards better inclusion of students with disabilities / Soud Louissi and Michelle Mielly -- Chapter 7. Education and resilience in the entrepreneurial university: An analysis of past and present practice at tangent, trinity's ideas workspace / Maeve O'Dwyer and Daniel Rogers -- Chapter 8. Resilience in education: Unveiling the covid-19 induced evolution of architecture pedagogy / Masoumeh Khanzadeh -- Chapter 9. Challenges and transformation of pedagogy towards blended learning: A sequential mixed-method study in higher education / Nagamani Nagaraja and Benny Godwin J. Davidson -- Chapter 10. Deglobalizing education: Perspectives, challenges and sustainability / Pratika Mishra and Aurobindo Kiriyakere -- Chapter 11. Technology-enabled education innovation: The hybrid teaching-learning process / J. Meenakumari, Ramakrishnan N, and Sriharish Ramakrishnan -- Chapter 12. Incorporation of deep learning based AI tools in education: A statistical evaluation of the perceptions of gen-z' and millennials / Remya Nair -- Chapter 13. Integrating AI tools in academic curriculum: A study
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Education, Higher; COVID-19 (Disease); Education -- Educational Policy & Reform -- General; Educational strategies and policy